Assessment of the Efficacy of ReoGo-J Robotic Training Against Other Rehabilitation Therapies for Upper-Limb Hemiplegia After Stroke: Protocol for a Randomized Controlled Trial - Takebayashi, Takashi; Takahashi, Kayoko; Amano, Satoru; Uchiyama, Yuki; Gosho, Masahiko; Domen, Kazuhisa; Hachisuka, Kenji (Frontiers in Neurology, 2018)
Background: Stroke patients experience chronic hemiparesis in their upper extremities leaving negative effects on quality of life. Robotic therapy is one method to recover arm function, but its research is still in its infancy. Research questions of this study is to investigate how to maximize the benefit of robotic therapy using ReoGo-J for arm hemiplegia in chronic stroke patients. Method: Design of this study is a multi-center parallel group trial following the prospective, randomized, open-label, blinded endpoint (PROBE) study model. Participants and setting will be 120 chronic stroke patients (over 6 months post-stroke) will be randomly allocated to three different rehabilitation protocols. In this study, the control group will receive 20 minutes of standard rehabilitation (conventional occupational therapy) and 40 minutes of self-training (i.e., sanding, placing and stretching). The robotic therapy group will receive 20 minutes of standard rehabilitation and 40 minutes of robotic therapy using ReoGo®-J device. The combined therapy group will receive 40 minutes of robotic therapy and 20 minutes of constraint-induced movement therapy (protocol to improve upper-limb use in ADL suggests). This study employs the Fugl-Meyer Assessment upper-limb score (primary outcome), other arm function measures and the Stroke Impact Scale score will be measured at baseline, 5 weeks, and 10 weeks of the treatment phase. In analysis of this study, we use the mixed effects model for repeated measures to compare changes in outcomes between groups at Week 5 and 10. The registration number of this study is UMIN000022509. Conclusion: This study is a feasible, multi-site randomized controlled trial to examine our hypothesis that combined training protocol could maximize the benefit of robotic therapy and best effective therapeutic strategy for patients with upper-limb hemiparesis.